Near‐Fatal ICD Lead Dysfunction with Implications for ICD Testing. Issue 1 (27th November 2015) - WUTZLER, ALEXANDER; ATTANASIO, PHILIPP; HAVERKAMP, WILHELM; BLASCHKE, FLORIAN
Abstract : A 31‐year‐old male patient with an implantable cardioverter defibrillator (ICD) experienced ventricular fibrillation. After resuscitation, no communication between the device and an ICD programmer was possible. The ICD was explanted, no signs of destruction were visible, and the ICD leads revealed normal values. A new ICD was implanted, interrogation values were stable. However, immediately after defibrillation testing the connection between programmer and ICD was interrupted and could not be established again. The device showed burn marks and a hole in the can. Analysis revealed an isolation defect of the ICD lead, which was not detectable with standard interrogation.